The Ukrainian agricultural sector and its main problems - Vzhytynska (Omelchenko), Kseniia (My University, 2021)
All agricultural markets will be negatively affected by the poor macroeconomic fundamentals in Ukraine. There will be limited investment into the country over the coming quarters given the unstable situation, which will affect agricultural production over forecast period. Russia's ban on imports from Ukraine will weigh on production for the dairy and livestock industries, as Russia represents one of Ukraine's largest agricultural export markets. Furthermore, significant currency depreciation will limit imports, hitting input usage and domestic investment. Ukraine is blessed with rich farming and forestry resources. Agriculture has traditionally been one of the most important sectors of the Ukrainian economy, given the high quality and availability of fertile land. More than two thirds (71,2%) of the total land area is agricultural land, compared to only 13,2% in Russia and 44,3% in the EU. Arable land at 32,5 million hectares has the largest area in Europe after Russia, accounting for 56,1% of the total land area – the highest percentage in Europe after Denmark. So, about 80 percent of the agricultural area is arable land, two-thirds of it the agriculturally rich "black soil". The primary food harvest products are barley, maize, potatoes, rice, soybeans, sugar beets, and wheat. Погані макроекономічні показники в Україні негативно вплинуть на всі сільськогосподарські ринки. Протягом найближчих кварталів інвестиції в країну будуть обмежені, враховуючи нестабільну ситуацію, яка вплине на сільськогосподарське виробництво протягом прогнозованого періоду. Заборона Росії на імпорт з України вплине на виробництво молочної та тваринницької промисловості, оскільки Росія є одним із найбільших експортних ринків сільськогосподарської продукції України. Крім того, значне знецінення валюти обмежить імпорт, вдарячи по використанню факторів виробництва та внутрішнім інвестиціям. Україна має багаті сільськогосподарські та лісові ресурси. Сільське господарство традиційно було однією з найважливіших галузей економіки України, зважаючи на високу якість і наявність родючих земель. Більше двох третин (71,2%) загальної площі землі займають сільськогосподарські угіддя, у порівнянні з лише 13,2% у Росії та 44,3% у ЄС. Площа ріллі в 32,5 мільйона гектарів займає найбільшу площу в Європі після Росії, займаючи 56,1% від загальної площі землі – найвищий відсоток у Європі після Данії. Так, близько 80 відсотків сільськогосподарських площ становлять орні землі, дві третини з них — сільськогосподарські «чорноземи». Основною продовольчою продукцією є ячмінь, кукурудза, картопля, рис, соя, цукровий буряк, пшениця.
Keywords: agricultural sector; agricultural enterprises; agro-industrial complex; land; agricultural markets; agricultural production; АПК; аграрні підприємства; земля; сільськогосподарська продукція; кафедра економічної теорії